Low incidence of vertebral fractures in early spondyloarthritis: 5-year prospective data of the DESIR cohort. Issue 1 (2nd November 2018) - Sahuguet, Julie; Fechtenbaum, Jacques; Molto, Anna; Etcheto, Adrien; López-Medina, Clementina; Richette, Pascal; Dougados, Maxime; Roux, Christian; Briot, Karine
Abstract : Objectives: An increased risk of vertebral fractures (VFs) has been reported in spondyloarthritis (SpA). Our hypothesis is that the prevalence of VFs is lower than reported in previous studies, especially in early SpA. This study aimed at assessing the incidence of radiographical VFs over 5 years in early axial SpA. Methods: The DESIR (DEvenir des Spondylarthropathies Indifférenciées Récentes) cohort, which included patients with inflammatory back pain highly suggestive of axial SpA, is the basis of this study. All radiographs of the DESIR cohort had been assessed at a central facility, by one investigator specialised in the field of the diagnosis of VFs according to Genant's method. We assessed the prevalence and incidence of VFs and vertebral deformities at baseline and over 5 years. Results: Five-year X-rays were available for 432 patients (mean age 34.3±8.7 years, 53% women). Diagnosis of VF was doubtful and needed adjudication for 19 patients (4.4%). 13 patients had prevalent VFs (3.0%) which were located at the thoracic spine (12 were grade 1). At 5 years, five patients had an incident VF (1.15%); seven vertebrae were fractured, mostly located at the thoracic spine (n=6/7), and of grade 1 (n=6/7). Conclusion: In the DESIR cohort, a population of early SpA, we found a low prevalence and incidence of VFs (3.0% and 1.15 %), respectively. This confirms our hypothesis that the actual prevalence and incidence of VFvertebral fracture in SpA is lower than that reported in the previous studies.